SENTINEL LYMPH NODE BIOPSY IN THE MANAGEMENT OF PATIENTS WITH MALIGNANT MELANOMA - Nguyen Canh, Tung; Nguyen Huu, Quang; Nguyen Hong, Son; Nguyen Dinh, Quan; Vu Nguyen, Binh; Le Thanh, Hien; Ta Thi Ha, Phuong; Vu Dinh, Tam; Nguyen Huu, Sau (Tạp chí Da liễu học Việt Nam, 2024)
Objectives: To evaluate the efficacy of sentinel lymph node biopsy in the treatment of malignant melanoma. Materials and Methods: Thirty-two melanoma patients without distant or clinical lymph node metastasis underwent preoperative lymphoscintigraphy using Tc99m and a handheld gamma probe to identify sentinel lymph nodes for biopsy. In cases with detected sentinel lymph node metastasis, the patient may require total complete lymph node dissection, combined with optional systemic therapy. Follow-up was performed to evaluate the efficacy of this procedure. Results: In 32 melanoma patients, the most common site of primary tumors was the extremity, accounting for 90.6%, with a mean Breslow index (thickness of the primary tumor) of 1.84 mm. The incidence of microscopic lymph node metastasis was 34.4%. For cases with no detected sentinel lymph node metastasis, 100% of patients had a stable condition, and no recurrence or metastasis was detected. In 11 cases with occult nodal metastasis: 2 deaths, 4 patients were treated with chemotherapy, and 5 cases without chemotherapy. The mean duration of hospitalization for the group with sentinel lymph node metastasis was greater than that of the group without sentinel lymph node metastasis, 25.1 ± 3.1 days and 13.5 ± 1.3 days, respectively. Conclusion: Our results suggest that sentinel lymph node biopsy is a less invasive technique for melanoma patients with no clinically detectable lymph node and distant metastases. This procedure has shown initial outcomes, but it is necessary to conduct a study with a larger sample size and a longer follow-up time, as well as comparing it with a control group for accurate evaluation. Received 23 June 2023 Revised 22 September 2023 Accepted 27 November 2023